Kejadian Anemia Ibu Hamil Di Wilayah Kepulauan - Jeini Ester Nelwan; Monisye Lesawengen1; Timothy Sean Kairupan; Oksfriani Jufri Sumampouw (STIKes Payung Negeri Pekanbaru, 2023)
Introduction: Anemia in pregnancy is one of the health problems in Indonesia, especially in archipelagic areas such as Sangihe Regency. Anemia in pregnancy caused by many factors such as age, knowledge, parity, gestational distance, nutritional status and ANC visits. The purpose of this study is to analyze the factors that influence the incidence of anemia in pregnant women in the island region. Method: : This is a correlational study with a cross-sectional approach. This research was conducted in the work area of ​​the Enemawira Health Center, Sangihe Islands Regency in April-October 2021. The respondents in this study were 61 pregnant women. Factors analyzed were age, knowledge, parity, gestational distance, nutritional status and ANC visits. The data obtained were analyzed univariatly and multivariatly. Results: The results of this study indicate that respondents are most widely distributed at the age of 20-35 years (59.0%), less knowledgeable (47.5%), 5 times parity (50.8%), pregnancy interval <2 years (70, 5%), poor nutritional status (62.3%), ANC visits <4 times (52.5%) and not anemia (55.7%). The results of this study also show that the variables of knowledge and ANC visits are the most influential variables on the incidence of anemia in in pregnancy in the island region. Conclusion: That can be concluded the most influential factors on the incidence of anemia in pregnant women in the archipelago are maternal knowledge about anemia and ANC visits. Based on this research, further research can examine the direct causes of anemia in pregnancy such as Fe intake and infectious diseases.